Hematology, Biochemistry Reference Intervals, and Morphological Description of Peripheral Blood Cells for a Captive Population of Crocodylus intermedius in Colombia - Barajas-Valero, Steven; Rodríguez-Almonacid, Cristian; Rojas-Sereno, Zulma; Moreno-Torres, Carlos; Matta, Nubia E. (Frontiers in Veterinary Science, 2021)
The Orinoco crocodile (Crocodylus intermedius, Graves, 1918) is the most threatened crocodilian of South America. There is only scarce information available about the physiology of this neotropical crocodile. This study's aim was to propose baseline hematological and biochemistry reference data and intervals, as well as a morphological description of the peripheral blood cells of captive Crocodylus intermedius. Blood was collected from 318 clinically healthy individuals maintained in captivity at Villavicencio - Colombia. Eight of these individuals were sampled and resampled, and these data were compared. Reference intervals were proposed for hematological values (PCV, RBC, WBC, MCV, MCH, MCHC, hemoglobin, and WBC differential counts) and biochemistries (TS, ALT, AST, ALP, LDH, CK, glucose, albumin, cholesterol, uric acid, creatinine, and lactate) including adults and juveniles, males and females’ crocodiles. Blood cell morphology for the species is described. Significant differences between sex and age were observed. Intraindividual analyze concluded differences for TS (P=<0,01) and RBC’s (P=<0,01). Some biochemical analytes showed a moderate correlation between them, such as ALT-ALP and ALT-UA.. We present here novel and baseline data with special importance for the clinical diagnosis, improving the national reintroduction programs from either in-situ and ex-situ populations.